Radical scavenging activities of peptide from Asian clam (Corbicula fluminea) and its protective effects on oxidative damage induced by hydrogen peroxide in HepG2 cells. Issue 3 (15th January 2020) - Xu, Hao; Lv, Shun; Jiang, Shaotong; Lu, Jianfeng; Lin, Lin
Abstract: The soft part of Asian clam ( Corbicula fluminea ) was hydrolyzed using trypsin and the hydrolysates were separated by ultrafiltration using the membrane with molecular weight cutoff of 10 and 5 kDa. Three fractions (F10000, F10000–5000, and F5000) were obtained. The F5000 showed the strongest scavenging abilities to DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl), superoxide anion, and hydroxyl radicals, and was further fractionated into four fractions (component I, II, III, and IV) by gel chromatography. The protective effects of these components on oxidative damage induced by hydrogen peroxide (H2 O2 ) in HepG2 cells were evaluated. Meanwhile, component I separated from F5000 had more positive effects on increasing the activity of catalase, decreasing lipid peroxidation, inhibiting H2 O2 ‐induced apoptosis, and higher yield. The component I was further separated using anion exchange chromatography and reversed phase high‐performance liquid chromatography, and the peptide sequence of Lys‐Gly‐Pro‐Ala‐ Pro‐Phe‐Tyr‐Pro‐Leu was identified by mass with molecular weight of 988.3 Da. Practical applications: Asian clam ( C. fluminea ) is used for liver protection in traditional Chinese medicine. The present study investigated the radical scavenging activity of the hydrolysates from C. fluminea and the protective effects of the hydrolysate fractions on oxidative damage induced by H2 O2 in HepG2 cells. In addition, a peptide was purified from the hydrolysate and the amino acid sequence of it was identified. Although chemical antioxidant has some side effects on health, the peptide with antioxidant activity obtained from C. fluminea would have more extensive application in food and nutraceutical.